2016
DOI: 10.1021/acs.organomet.6b00237
|View full text |Cite
|
Sign up to set email alerts
|

Effective Antitumor Candidates Based upon Ferrocenylseleno-Dopamine Derivatives: Growth Inhibition by Induction Cell Apoptosis and Antivascular Effects

Abstract: One ferrocenyl-dopamine (L1) and four ferrocenylseleno-dopamine derivatives (L2−L5) were designed and prepared with different structural parameters, such as chalcogen atoms, cycle, and semirigidity. The best in vitro anticancer activity occurred with 1,5-diselena[8]ferrocenophane L5, which inhibited cancer cell growth at the lowest micromolar concentrations. The biological studies showed that L5 arrested the cell cycle in G1 phase and induced apoptosis by activating caspase 3/9, also inhibiting endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…However, the IC 50 value of compounds 3 and 7 were more potent than compounds 15 and 19 , though the IC 50 value of compound 11 was less potent than compound 23 . These results suggest the half-wave may have an impact on the cytotoxicity of those cyclopalladated candidates, but it was not a major factor …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the IC 50 value of compounds 3 and 7 were more potent than compounds 15 and 19 , though the IC 50 value of compound 11 was less potent than compound 23 . These results suggest the half-wave may have an impact on the cytotoxicity of those cyclopalladated candidates, but it was not a major factor …”
Section: Resultsmentioning
confidence: 88%
“…The cyclic voltammograms (CVs) were recorded as a reported method . In brief, the methanol/acetonitrile (v/v 1/1) solution was used as the electrolyte with 0.1 M [NBu 4 ]­[PF 6 ] as the supporting electrolyte.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The six new derivatives, F1c, F1d, F2b, F3b, F4a and F4b, were synthesized following the reported methods as shown in Scheme S1, † 12 and the detailed synthetic processes and related characterization data are provided in the ESI. † Spectroscopic studies were carried out and confirmed the structure of the as-prepared compounds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10] Up to now, the ferrocifen family developed mainly by Jaouen's group is one of the real breakthroughs in modern medicinal organometallic chemistry as anticancer drug candidates. [5][6][7]9 Inspired by the promising biological activity of ferrocenyl selenoethers, [11][12][13] our group has previously reported a series of ferrocenylseleno-dopamine derivatives with dopamine units on the backbone, F1a, F1b, F2a and F3a listed in Table 1. These compounds were found to induce carcinoma cell apoptosis and inhibit angiogenesis of vessels in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation